An Analysis of Socio-economic, Marketing and Management Constraints Faced by Beneficiaries after the Integrated Fisheries Development Scheme in Khammam District of Telangana - Kishor. K. M; I. Krishna Teja; K. Suhasini; M. Shyam Prasad; K. Supriya (Archives of Current Research International, 2024)
Aims: This study typically aims to analyze the multifaceted challenges faced by fishers who are the beneficiaries of the Integrated Fisheries Development Scheme (IFDS) in Khammam District of Telangana. Study Design: Ex-post facto research design was used for the study and revealed the constraints faced by beneficiaries after IFDS. Place and Duration of Study: The study was held in Khammam district of Telangana. In Khammam district top 5 mandals with the highest number of beneficiaries were selected for the study. The study lasts from April to May 2024. Methodology: A three-stage random sampling technique was selected for the study with a sampling population of 120 beneficiaries. A well-structured pretested interview schedule was prepared that includes major constraints faced by respondents regarding socio-economic, marketing, and management challenges they faced after IFDS. The constraints were selected from previous literature. Based on ranks given to the listed constraints by respondents, the ranks were analyzed and conclusive results were drawn by using Garette’s ranking Technique. Results: The prime constraint with higher mean score values identified in these categories are in socio-economic constraints where problems in availing loans and insurance with mean score values of 72.06 and 66.31 respectively. In marketing constraints, Lack of proper market infrastructure (73.31) and Lack of processing facilities (61.61) were observed as major constraints. In management constraints, prime constraints observed were the high cost of material inputs (72) and high labor cost (59.91). Along with these major constraints some minor constraints were also identified in the study. Conclusion: Through a comprehensive examination of these constraints, the study seeks to offer insights that can assist policymakers, practitioners, and stakeholders in developing strategies to address the challenges encountered by beneficiaries of IFDS in the Khammam district of Telangana. This could potentially have a significant impact on fish productivity and the livelihood of fishers across the state.